New materials in civil engineering - Samui, Pijush, 1978-; Kim, Dookie, 1969-; Iyer, Nagesh R.; Chaudhary, Sandeep (Butterworth-Heinemann, an imprint of Elsevier, 2020)
"New Materials in Civil Engineering provides engineers and scientists with the tools and methods needed to meet the challenge of designing and constructing more resilient and sustainable infrastructures. This book is a valuable guide to the properties, selection criteria, products, applications, lifecycle and recyclability of advanced materials. It presents an A-to-Z approach to all types of materials, highlighting their key performance properties, principal characteristics and applications. Traditional materials covered include concrete, soil, steel, timber, fly ash, geosynthetic, fiber-reinforced concrete, smart materials, carbon fiber and reinforced polymers. In addition, the book covers nanotechnology and biotechnology in the development of new materials."--Publisher's description.